PEMBINAAN PROFESIONALISME DI BIDANG DI SEKOLAH TINGGI PARIWISATA BANDUNG - Chandra, Teddy (Universitas Pendidikan Indonesia, 2017)
The aim of this research is to learn about Professionalism Development In Hospitality at Bandung Tourism of Higher Education qualitatively. The result of this research shows that the professionalism development programme in Bandung Tourism of Higher Education has been done as a part of education system. The research also shows every professionalism development problem that need to be solve sustainably.